2022
DOI: 10.21203/rs.3.rs-1720726/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HDAC1 and HDAC6 are essential for driving growth in IDH1 mutant glioma

Abstract: Introduction: Low-grade and secondary high-grade gliomas frequently contain a mutation in the IDH1 metabolic enzyme that is hypothesized to drive tumorigenesis by inhibiting many of the chromatin-regulating enzymes that regulate DNA structure. Much of the previous research has focused on DNA methylation leaving histone modifications relatively under-studied. Histone deacetylase inhibitors are promising anti-cancer agents and have already been used in clinical trials, however a clear understanding of their mech… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 59 publications
2
3
0
Order By: Relevance
“…Notably, these genes, namely FvH4_3g16760 and FvH4_5g27840, paly crucial roles in the GA metabolic and signalling pathway (Figure 7). One plausible explanation for this finding is that in the knockout mutants, other members of the SRT family compensate for the absence of FvSRT1, as in line with the previous observation (Garrett et al, 2023). In summary, our findings highlight that FaSRT1-2 exerts regulatory control over strawberry plant growth, development, and morphogenesis through its influence on ABA and GA 3 as well as modulation of key genes expression in the signalling pathway.…”
Section: Discussionsupporting
confidence: 90%
“…Notably, these genes, namely FvH4_3g16760 and FvH4_5g27840, paly crucial roles in the GA metabolic and signalling pathway (Figure 7). One plausible explanation for this finding is that in the knockout mutants, other members of the SRT family compensate for the absence of FvSRT1, as in line with the previous observation (Garrett et al, 2023). In summary, our findings highlight that FaSRT1-2 exerts regulatory control over strawberry plant growth, development, and morphogenesis through its influence on ABA and GA 3 as well as modulation of key genes expression in the signalling pathway.…”
Section: Discussionsupporting
confidence: 90%
“…We next re-analyzed our previously published RNA-seq and ATAC-seq dataset 15 of IDH1 MT and IDH1 WT cell lines treated with 1mM VPA for 5 days and found that similar to the current findings, VPA treatment increased a greater number of genes and downregulated a smaller number of genes in both IDH1 WT and IDH1 MT cell lines (Fig3G). Interestingly, ATAC seq analysis showed that despite of the relatively increased transcription, a greater number of peaks were lost and only a few peaks were gained after VPA treatment (Fig3H), suggesting VPA treatment activates transcription but paradoxically results in chromatin condensation.…”
Section: Vpa Has Opposing Effects On Overall Gene Expression and Chro...supporting
confidence: 81%
“…Next, we wondered whether the effect of VPA on lipogenic genes is dependent or independent of HDAC inhibition. We re-analyzed RNA seq data from our recently published work 15 in which shRNAs used to knockdown different HDACs in IDH1 MT cell line HK252 to assess the effects on fatty acid metabolism genes. We found that knockdown of HDAC2,3,4, & 9 increased expression of lipogenic genes such FASN, stearyl coA desaturase (SCD) and HMGCR.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations